Comparison of course of infections and antibiotherapy in patients with and without diabetes mellitus - one center experience - Maria Stec; Agata Suleja; Wiktoria Kuczmik; Aleksandra Mroskowiak; Maciej Migacz; Michał Holecki (Śląski Uniwersytet Medyczny w Katowicach, 2023)
INTRODUCTION: Infections affect all patients, including those with diabetes mellitus (DM), which can determine the course of infection. The aim of the study was to compare the course and treatment of infection in patients with DM and without DM. MATERIAL AND METHODS: 180 medical records of patients hospitalized in 2021 at the Department of Internal Medicine, Autoimmune and Metabolic Diseases in Katowice, with infections were analyzed. The analysis included age, sex, clinical diagnosis, DM treatment, antibiotic therapy, and laboratory parameters. The Statistica program was used for statistical analysis. RESULTS: The most prevalent reasons for hospitalization in both groups were: pneumonia in the course of COVID-19 (35.5% DM vs 33.7% non-DM) and urinary tract infections (26.3% DM vs 19.2% non-DM). Significantly more non-DM patients required polyantibiotic treatment (69.7% DM vs 89.4% non-DM). The most frequently used antibiotics were β-lactams (59.2% DM vs 57.7% non-DM). In-hospital mortality was 20% (21% DM vs 19.2% non-DM). The length of hospitalization was 1-35 days, the median in the whole group was 9 days (10 days DM vs 8 days non-DM). Both the initial and terminal CRP concentrations were analyzed. The median of the initial value was 71.6 (72.3 DM vs 66.2 non-DM) and the median of the terminal value was 17.15 (17.9 DM vs 15.3 non-DM). The glucose concentration on admission was assessed with the median 123.5 mg/dL (156 mg/dL DM vs 107 mg/dL non-DM). CONCLUSIONS: Many DM complications are well known, yet the course and treatment of infection do not differ significantly in patients with DM and without DM. Despite that, each patient should be considered individually, so the chosen treatment constitutes an optimized therapy.